Two-photon absorption of few-electron heavy ions - Surzhykov, Andrey; Indelicato, P.; Santos, J. P.; Amaro, P.; Fritzsche, S. (Physical review. A, Atomic, molecular, and optical physics, 2011)
The two-photon absorption of few-electron ions has been studied by using second-order perturbation theory and Dirac's relativistic equation. Within this framework, the general expressions for the excitation cross sections and rates are derived including a full account of the higher-order multipole terms in the expansion of the electron-photon interaction. While these expressions can be applied to any ion, independent of its particular shell structure, detailed computations are carried out for the two-photon absorption of hydrogen-, helium-, and berylliumlike ions and are compared with the available theoretical and experimental data. The importance of relativistic and nondipole effects in the analysis and computation of induced two-photon transitions is pointed out. Moreover, we discuss the potential of these transitions for atomic parity-violation studies in the high-Z domain.
Gesehen am 26.10.2022